2022
DOI: 10.1364/prj.459897
|View full text |Cite
|
Sign up to set email alerts
|

Multi-step in situ interface modification method for emission enhancement in semipolar deep-ultraviolet light emitting diodes

Abstract: Semipolar III-nitrides have attracted increasing attention in applications of optoelectronic devices due to the much reduced polarization field. A high-quality semipolar AlN template is the building block of semipolar AlGaN-based deep-ultraviolet light emitting diodes (DUV LEDs), and thus deserves special attention. In this work, a multi-step in situ interface modification technique is developed for the first time, to our knowledge, to achieve high-quality semipolar AlN templates. The stacking faults were effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Overall, the in situ thermal-treated sample shows much narrower XRD RC linewidths, suggesting a lower defect density and better crystal quality than the HTA sample. The efficient blocking and annihilation of stacking faults in the in situ-treated sample can be ascribed to the interface modification process as previously demonstrated in our work [13]. Specifically, the stacking faults were efficiently blocked due to the modification of atomic configurations at the related interfaces.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Overall, the in situ thermal-treated sample shows much narrower XRD RC linewidths, suggesting a lower defect density and better crystal quality than the HTA sample. The efficient blocking and annihilation of stacking faults in the in situ-treated sample can be ascribed to the interface modification process as previously demonstrated in our work [13]. Specifically, the stacking faults were efficiently blocked due to the modification of atomic configurations at the related interfaces.…”
Section: Resultssupporting
confidence: 76%
“…However, the ex situ annealing technique poses a growth because large residual strains are built up. Rece situ treatment technique that greatly improves the crysta on the semipolar AlN template, ultimately achieving a s nescence intensity [13]. The in situ treatment technique cient method for the preparation of high-quality semipo toward the realization of high-efficiency optoelectronic d ing of the optical behaviors of the semipolar DUV-LED g situ-annealed AlN template is strongly desired.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, high-temperature annealing (HTA) of sputtered AlN films has been widely investigated to promote the development of high-quality nitride films on different face sapphire substrates. HTA and regrowth processes are adopted as stable and effective methods in the realization of high luminous efficiency LEDs. , For c-plane nitride materials and devices, Weyers et al revealed that the performance of DUV LEDs could be significantly improved due to strain management and defect reduction using two annealing steps . Wang et al studied the power enhancement of the 265 nm DUV-LED flip-chip based on an annealed hydride vapor phase epitaxy-AlN (HVPE-AlN) .…”
Section: Introductionmentioning
confidence: 99%